Are Physical Education Policies Working? A Snapshot From San Francisco, 2011 - Hannah R. Thompson, MPH; Jennifer Linchey; Kristine A. Madsen, MD, MPH (Centers for Disease Control and Prevention, 2013)
Introduction School physical education (PE) has been identified as a critical public health tool to increase physical activity among youths. We sought to objectively assess compliance with PE quantity mandates and quality recommendations in a large urban California school district. Methods We collected PE schedules and systematically observed PE lessons (n = 154) in 20 elementary, 4 middle, and 4 high schools from February through May 2011. Results On the basis of schools' master schedules, 83% of elementary schools met the California state mandate of 100 PE minutes per week. Teachers' actual schedules indicated that 20% of schools met the mandate, and observation showed that only 5% were in compliance. All middle and high schools met the mandated 200 minutes per week. On average, classes at all school levels met the recommended 50% of PE lesson time in moderate-to-vigorous physical activity. No teacher- or school-level factors significantly predicted PE quantity, but credentialed elementary PE teachers spent more time building students' motor skills. Conclusions Our results suggest that current national estimates of PE, which are based on schools' self-report, overestimate the amount of PE provided in elementary schools. Although more than half of PE class time was spent in moderate-to-vigorous physical activity, total physical activity in elementary schools from PE is minimal and may do little to contribute to students' overall health.